Adding an underwire in bras decreases breast motion and discomfort during locomotion. Issue 1 (February 2021) - Chen, X; Sheng, X; Sun, G; Li, Y; Lake, M J; Xie, H
Abstract: The aim of this study was to determine whether exercise-induced vertical breast motion and discomfort in women with large breasts decrease when an underwired bra is used compared with when an underwire-free bra is worn. Vertical breast displacement was assessed in nine women (C cup size) who exercised on a treadmill in two bra conditions: underwired bra and underwire-free bra. Perceived breast motion and discomfort were reported by each participant using the visual analogue scale after each bra condition trial. Vertical breast displacement and perceived breast motion and discomfort were compared between the two bra conditions. Vertical breast displacement (p < 0.05) and perceived breast motion (p = 0.007) and discomfort (p = 0.025) were significantly lower in the underwired bra condition than in the underwire-free bra condition. The bra design feature of containing an underwire was effective in decreasing exercise-induced vertical breast motion and discomfort among the women with large breasts. The current research is the first study to explore the effects of including a bra underwire on the change in breast motion and discomfort.